Investigating the Effect of Testosterone Supplement on Heart and Muscle Damage in Rats Applied with Swimming Exercise - Ömer Kulaksız; Sefa Lök (Türk Spor ve Egzersiz Dergisi)
Anabolic Androgenic Steroids which are a synthetic derivative of testosterone are known to be used by some sportsmen in order to improve performance. The present study was conducted to investigate the effect of testosterone supplement on heart and muscle damage in rats applied with swimming exercise. The study was conducted on 30 day-old 27 (Wistar, male) rats that were supplied from “Selçuk University Experimental Medicine Research and Application Center”. The rats were divided into 4 groups. The rats in control groups (n:6) were fed during the study without doing any application. The rats in testosteronegroup (n:7) were supplied with a 10 mg/kg dose of testosterone 5 days a week for 3 weeks. The rats in exercise group (n:7) did freestyle swimming exercise for 30 minutes a day for 5 days a weekfor 3 weeks. The rats in testosterone + exercise group (n:7) did freestyle swimming exercise for 30 minutes and were administered with 10 mg/kg dose of testosterone supplement for 5 days a week for 3 weeks. At the end of the trial, necessary biochemical parameters were measured in serums obtained by drawing blood from tails of the rats. While levels of Serum, LDH, CK-MB, and CKwere studied by using an autoanalyzer, Troponin I level was analyzed by using ELISA kit. SPSS 15.0 packaged software was usedin statistical evaluation of the data and the results were given as mean±SE. Since the data were convenient with the normal distribution, ANOVA test was applied for betweengroups comparison and Duncan test was used to identify from which group the difference was resulted. When between-groups values of troponin I, ck-MB, and LDH, which are indicators of heart damage, and enzyme CK, which is an indicator of muscle damage,for control, exercise, testosterone, and testosterone+exercise groups were compared, a statistically significant difference was determined between control, exercise, testosterone, and testosterone+exercise groups (p lt;0.05). As a result of statistically analysis performed on all groups, the difference was found to be caused by testosterone and testosterone+exercise groups. Because testosterone production is naturally increased in the body during the exercise, swimming exercise and testosterone administration led to significant occurrence of troponin I, ck-MB, LDH, which are heart damage indicators in rats, and CK value, which is an indicator of muscle damage, in the blood.